The contribution of Presbyterianism to the Maritime Provinces of Canada - Scobie, Charlie, 1932-; Rawlyk, George A. (McGill-Queen's studies in the history of religion., 1997)
"In their assessment of the contribution of Presbyterianism to the history and culture of the Maritime provinces, contributors from a variety of disciplines provide fresh and fascinating explorations of the significance of Presbyterianism in such areas as education, literature, social influence, and missionary outreach."--Jacket